ANALISIS KADAR DETERGENT ANIONIK PADA SEDIAAN PASTA GIGI ANAK-ANAK - Endang Triwahyuni M; Wikanastri Hersoelistyorini (JURNAL KESEHATAN, 2009)
Abstract Background: Tooth paste is one of the cosmetics product used not only by adult but also children. The Function is to clean teeth from food or beverages scrap, to keep the health of teeth and gum, and also to reduce the smell caused by mouth bacteria. Tooth paste is made from several ingredients; among other is the surfactant that can form foam from toothpaste. Surfactant is usually added in a form of synthetic detergent because it can give fictive foaming effect in a form of anionic detergent. The use of surfactant in tooth paste is low spread and to wet the particles found in tooth paste. The surfactant has to be able to create liquid Suspension from the polishing materials during the process of brushing the teeth and make it able to dissolve into the pit of teeth in order to accelerate the cleaning effect and getting rid the unknown substances. Some other surfactant can also lower the surface pressure in order to make toothpaste absorb into the teeth surface Pores and fictively dissolving the dirt attached to the teeth. According to Harry's Cosmeticologt, the amount of surfactant allowed in tooth paste is around l%-2%. Population o/ the Research: The sample used in this research is the children's toothpaste taken using the random sampling method out of various brands and flavors. Each simple is analyzed using triple method. Result of the Research: The result of the research is as shown: l) Anionic detergent amount found in Children toothpaste sample A = 0,15%o, sample B = 0,06%, sample C = 0,04%, sample D = 0,050%, sample E =0, 13%, sample F=0,30%,sampleG=0,35%,sampleH=0,lToldansamplel=0,28%. 2)Anionic detergent amount found in children tooth paste being researched fulfill the Harry's Cosmeticologt criteria that says the amount of anionic detergent or surfactant found in toothpaste should not be more than 2%o. Keywords: analysis on amount, anionic detergent, children's Tooth paste